Forensic facial identification : theory and practice of identification from eyewitnesses, composites and CCTV - Valentine, Tim, 1959-; Davis, Josh P. (Wiley series in psychology of crime, policing, and law., 2015)
AND CONCLUSIONREFERENCES; 8 Confidence and Accuracy of Eyewitness Identification; PERCEPTIONS OF EYEWITNESS CONFIDENCE IN LEGAL SETTINGS; THEORETICAL PERSPECTIVES ON THE CA RELATIONSHIP; RESEARCH ON THE CONFIDENCE-ACCURACY RELATIONSHIP FOR EYEWITNESS IDENTIFICATION DECISIONS; APPLIED FACTORS THAT LIMIT THE EFFECTIVE USE OF CONFIDENCE; A NOVEL USE FOR EYEWITNESS CONFIDENCE: CONFIDENCE AS AN INDEX OF RECOGNITION; REFERENCES; Part 4: Identification from CCTV Images; 9 Human Verification of Identity from Photographic Images; THE USE OF PHOTOGRAPHIC IMAGES IN COURT.